The spine of night [videorecording (DVD)] - King, Morgan Galen; Gelatt, Philip (RLJE Films, 2022)
An ambitious young man steals forbidden knowledge from a sacred plant. He falls to its darker temptations and in so doing, unleashes ages of suffering onto mankind. As his power grows over the years, those who stand against him are a daring tomb robber, star-crossed lovers, a maniacal necromancer, winged assassins, and an undying guardian.